Perbandingan Performa Algoritma Md5 Dan Sha-256 Dalam Membangkitkan Identitas File - Saputra, Imam; Nasution, Surya Darma (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The ease of accessing the internet makes it very easy for humans to share various kinds of files. These files are very easy to download, so it is not uncommon for these files to become duplicates or the same files are stored on personal storage media. This of course will take up personal storage space owned. To avoid this, the steps that can be taken are to provide the identity of each file that represents the contents of the file. So that it can be known whether the contents of the file are the same or not. To generate the identity of a file, a special algorithm is needed that can represent the contents of the file. Algorithms that can be used to generate file identities are algorithms that fall into the hash function category. But in its development there are many algorithms in hash functions that can be used to generate file identities. The algorithms that are often used are the MD5 algorithm and the SHA-256 algorithm. The MD5 and SHA-256 algorithms have different algorithm structures so they have different performance when generating the identity of a file. By comparing the performance between the MD5 and SHA-256 algorithms, we will get an algorithm that has better performance when used to generate file identities.